UJI PEMBERIAN BERBAGAI KOMPOS ORGANIK DAN PUPUK ORGANIK CAIR (POC) KULIT PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAHE MERAH (Zingiber officinale Rosc. Var. Rubrum) - T. Alfino Mustava; Sulhaswardi (DINAMIKA PERTANIAN, 2022)
The purpose of this study was to determine the effect of the interaction of various organic composts and banana peel POCs on the growth and production of red ginger (Zingiber officinale var Rubrum). This study used a Factorial Completely Randomized Design (CRD), which consisted of two factors and 3 replications. The first factor was various organic compost (P), consisting of 4 levels, namely 0.600 (Vegetable Compost), 600 (Ketapang Compost), 600 (Straw Compost) g/plant and the second factor was banana peel organic fertilizer which consisted of 4 levels, namely 0, 125, 250, and 375 ml/L of water. Parameters observed were plant height (cm), number of tillers (stem), the weight of wet safe (g), wet weight of rhizome (g), dry weight of rhizome (g), and harvest index (g). The data were statistically analyzed and continued to the BNJ test at the 5% level. The results showed that the interaction of various organic compost and banana peel POC treatments affected the number of clumps of tillers (stems), wet rhizome weight (g), wet rhizome weight (g), and dry rhizome weight (g). The best treatment was found on a combination of 600 g/Plot Straw Compost and Banana Peel POC with a dose of 375 ml/L water. The main effect of various organic composts affects all parameters of the observation with the best treatment was the 600 g/plant Ketapang Compost. The main effect of POC Banana Peel affected the observation parameters Wet rhizome Weight (grams), Wet Rhizome Weight (grams), Dry Rhizome Weight (grams), and Harvest Index. The best dose for POC Banana Peel Treatment ws 375 ml/L water.